AL-FARABI – GREAT MUSLIM PHILOSOPHER, MATHEMATICIAN AND TEACHER - Al-Hamza М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This work is devoted to Al-Farabi as a scientist and a person, about his philosophical and mathematical works and his main approach to life and science as a classification of sciences (enumeration of sciences), and here it should be emphasized that Al-Farabi combined theory and practice into a single, he considered a scientist is not only a creator of scientific ideas, but also must be a person of virtue in society. Its main ideological platform was philosophy and logic. And, as they say in Arabic الفلسفففففففففف أم العلوم) i.e. philosophy is the mother of sciences). He followed the great Greek philosophers Aristotle (the first teacher) and Plato. And it is no coincidence that Al-Farabi became known as the "second teacher", and this is due to the fact that he deeply assimilated Greek philosophical knowledge, perfectly commented on it and corrected it when needed.